Linear Polyubiquitin Chain Modification of TDP-43-Positive Neuronal Cytoplasmic Inclusions in Amyotrophic Lateral Sclerosis. Issue 3 (16th December 2019) - Nakayama, Yoshiaki; Tsuji, Kazumi; Ayaki, Takashi; Mori, Megumi; Tokunaga, Fuminori; Ito, Hidefumi
Abstract: Neuronal cytoplasmic inclusions (NCIs) containing TAR DNA-binding protein of 43 kDa (TDP-43) are pathological hallmarks of amyotrophic lateral sclerosis (ALS) and are known to be ubiquitinated. Eight linkage types of polyubiquitin chains have been reported, each type of chain exerting different intracellular actions. The linkage type of polyubiquitin chain involved in the formation of NCIs in sporadic ALS (sALS), however, has not yet been elucidated. We performed immunohistochemical study of the spinal cords of 12 patients with sALS and on those of 6 control subjects. Virtually all ubiquitinated NCIs were immunolabeled with lysine 48-linked polyubiquitin chain (K48-Ub). Although the majority of NCIs were triple-immunoreactive for K48-Ub, linear polyubiquitin chain (L-Ub), and lysine 63-linked polyubiquitin chain (K63-Ub), thin parts of K48-Ub-immunopositive NCIs were not labeled for K63-Ub or L-Ub. We also detected HOIP and SHARPIN, components of linear ubiquitin chain assembly complex, colocalizing with L-Ub on NCIs. Moreover, the immunosignal of optineurin, an autophagy receptor working with L-Ub, and that of activated NF-κB p65, were observed to be colocalizing with L-Ub on certain parts of NCIs. The L-Ub modification of TDP-43-positive NCIs may function as an inducer of autophagic clearance of NCIs, neuroinflammation, and neurodegeneration in sALS.